Minutes of collegiate bodies: relevance, pertinence and reflection of the substantive action of the organizations - Ugalde Villalobos, María Eugenia (2020)
The objective of this article is to provide information about the process of taking minutes not only in person but also virtually. The writing of minutes of collegiate or deliberative bodies is a subject that requires analysis from different aspects: technical, administrative, legal, structural, and drafting procedures. Everything is evidenced from the national regulations for public bodies as specialized criteria and theorical basis. The methodology used was based on a relevant bibliographic inquiry and the opinion of people in charge of participating in the taking of minutes, both in governmental and private organizations. The results show the importance of the minutes of collegiate bodies as a historical and current documentary type that reflects the substantive actionof the instances, either by a guideline that establishes it, or by the pertinent recognition of its use and application.